Health Literacy, Media Exposure and Behavior Among Young Adults During the Covid-19 Pandemic - Riza Hayati Ifroh; Tanti Asrianti (Faculty of Public Health, Sriwijaya University, 2020)
Indonesia has published and released a new normal life, even though the COVID-19 rate continues to increase. The term of new normal life includes specific preventive behaviors as daily activity and supported skill by adequate health literacy of COVID-19. The purpose of this study was first to analyze the correlation of information media exposure to health literacy levels of COVID-19 and second to analyze the correlation between health literacy levels of COVID-19, exposure of information media to the adaptive behavior in COVID-19 prevention of young adult in East Kalimantan. The research design was a cross-sectional, quantitative study. The sampling technique used accidental sampling (254 young adults) data was taken by Google form. In data analysis to determine the correlation between gender to the level of health literacy of COVID-19 and new normal life used the Chi-square test. The analysis of age, exposure of mass and non-mass media to the level of health literacy of COVID-19 and, HL to new normal life behavior by using Spearman analysis test. The result statistics by gender (p=0.748), age (p=0.323), and health literacy level of COVID-19 (p=0.788) were not associated with the behavior of transmission of COVID-19 and prevention in new normal life. The variable of information exposure (by non-mass media and mass media) has a significant value associated with the variable of the behavior of new normal life (p-value <0.001). The higher exposure of information media through mass and non-mass media have a correlation to increasing the health literacy level of COVID-19 and behavior to prevent the disease.